GE_GERICHTE P/7146/2018 vom 20. Juni 2018 - GE Cour de justice (2018)
ERREUR SUR LES FAITS(DROIT PÉNAL) ; RECHERCHE SECRÈTE ; INVESTIGATION SECRÈTE ; ENTRÉE ILLÉGALE | CPP.10; CPP.289; CPP.298.letA; CP.12; CP.13; LEtr.115.al1; LEtr.115.al3